The adoption of Knowledge Management Systems (KMS) among academicians in Nigeria universities - Salami, Ahmed; Suhaimi, Mohd Adam (Kulliyyah of Information and Communication Technology, IIUM, 2019)
Higher Education Institution (HEI) is known as the knowledge hub where knowledge is acquired and shared among all. In order for the Nigerian universities to fully realize its knowledge management related objectives, there should be a requirement of supporting knowledge management system as these universities also face various challenges regarding this system, including whether or not to adopt it, whether users would accept to work with it.This study reports the factors of adoption of KMS among academicians in Nigeria. The following four major independent variables were studied i.e. 1) Organization (Structure, Government support, Culture, and organizational infrastructure), 2) Individual (Knowledge, Personal innovativeness, experience, and attitude), 3) Management Support (training, management initiatives and management) and 4) technology (trialiability, compatibility, visibility and complexity. The study employed an explanatory quantitative method design using survey. Findings identified that individual and management support factors play a major role on the adoption of KMS in Nigeria than organizational and technological factors. Using these findings, future researchers can further verify and explore in more depth on factors for KMS adoption especially the management support and individual factors.